Hysterectomy to the Unicornuate Uterus Suffering of Hematometra - Cepi T Pramayadi; Imma Nurliana; Erliana Fani (Indonesian Society of Obstetrics and Gynecology, 2017)
Objective: Unicornuate uterus with rudimentary cavity is an extremely rare Mullerian duct anomaly. It is frequently misdiagnosed or under treated, since women who suffer from this condition tend to be asymptomatic. We aimed to report this interesting case and review the available background literature. Methods: Case report. Case: A thirty two-year-old nulligravid woman was presented with severe abdominal pain. Laparoscopic surgery demonstrated unicornuate uterus with arudimentary cavity and hematometra. Partial hysterectomy was conducted to the right rudimentary uterus. Conclusion: Thorough diagnosis is essential to prevent the complications of unicornuate uterus. Unicornuate uterus with rudimentary cavity is associated with increased rate of pregnancy complications such as preterm labor and fetal malpresentation. Pregnancy can also occurred on the rudimentary cavity and leads to recurrent pregnancy loss. Laparoscopy is essential for confirmatory diagnosis. Surgical intervention should be considered as the first line therapy to avoid associated morbidity. [Indones J Obstet Gynecol 2017; 5-4: 246-249] Keywords: hematometra, hysterectomy, unicornuate uterus